Proceedings of the IV OdontoMeeting / X CEAJO - Anbinder, Ana Lia; Pinto de Mendonça, Rafael (Brazilian Dental Science, 2023)
The IV Odontomeeting, initially scheduled for 2021 but postponed due to the pandemic and ICT renovations, finally took place from October 18 to 20, 2023. The congress welcomed approximately 500 undergraduate and postgraduate students, as well as professionals from the Vale do Paraíba region. The event returned with the theme "Innovation, Art, and Care," carefully chosen to highlight the necessary interconnection between science and humanism during these ongoing challenging times. This theme permeated the entire schedule of lectures and cultural activities throughout the event.In the 12 months leading up to the event, 10 pre-events were organized, featuring lectures from diverse areas, cultural activities, and philanthropic community actions—a significant effort to revive collective activities in the post-pandemic scenario.During the event, there were 31 speakers from various fields of dentistry, in addition to 109 scientific paper presentations across 9 categories. Now, we have the great opportunity to have the abstracts published in this special supplement of Brazilian Dental Science.The meeting garnered support from various sponsors, fostering a closer relationship between the university and businesses. Among the attendees were dentists working for the Municipal Government of São José dos Campos, as part of a partnership between the University and the public service.Besides the scientific program, cultural activities took center stage, featuring music, dance, theater, exhibitions, and a book launch—an endeavor to highlight the association between art and science. It was heartening to see the ICT community come together for a common goal and celebration. I express my gratitude to everyone who participated in this endeavor and wish success to the V Odontomeeting! The countdown hasalreadybegun!Prof. Dr. Ana Lia AnbinderPresident of the IV OdontoMeeting / X CEAJO